Review of Procedures for Reconstruction of Soft Tissue Chest Wall Defects Following Advanced Breast Malignancies. (31st January 2019) - Billington, Alicia; Dayicioglu, Deniz; Smith, Paul; Kiluk, John
The purpose of this article is to review closure options for complex chest wounds in patients with locally advanced breast cancer. Experiences of the plastic and oncologic surgery teams at Moffitt Cancer Center were reviewed, and the literature researched for various surgical options of complex chest wound closure. Multiple treatment modalities exist for reconstruction of complex chest wall wounds with the external oblique and V-Y latissimus dorsi musculocutaneous advancement flaps serving as workhorses in reconstruction. Treatment of cancer has moved from simply a surgical solution to include other modalities such as hormonal therapy, chemotherapy, and radiation—the latter 2 having serious consequences for wound healing. A team approach and knowledge of available flap options are vital for closure of complex wounds in a timely manner. Appropriate planning can optimize the primary goal of the oncologic surgeon to remove the cancer and the plastic surgeon's objective to reconstruct the defect and achieve a closed, durable wound prior to chemotherapy and radiation. We present the experience at the Moffitt Cancer Center in reconstructing challenging chest defects and review the reconstructive ladder.